The American Impact: How American Culture Has Been Reshaping English Language Learning In and Out of the Classroom - Váczi, Zsombor (AMERICANA E-journal of American Studies in Hungary, 2024)
In numerous countries around the world as well as in Hungary since the appearance of English as a Foreign Language in the classroom, British English has always been set as the standard variety to be taught. The vast majority, if not all, of the course books used in the Hungarian classrooms are based upon or prioritize British English. Hardly ever will a language learner hear American voices in the audio materials that accompany a course book series. The boom of technology in the twenty-first century, the proliferation of the digital world and the growing popularity of social media have long opened the doors to a conspicuous American impact with regard to content consumption among teenagers. In the past years, students have been zealously discussing American songs, movies, TV series, streaming services, video channels, influencers or computer games. The language varieties they encounter in such contents often stand in conflict with the language varieties their course book materials offer. A small-scale study carried out with the participation of about 100 students between the ages of 13 and 19 sets out to reveal which varieties of English students prefer nowadays based on their content consumption. The study relies on an anonymous online survey consisting of both closed- and open-ended questions. The results aim to provide a key to how we teachers of English should change our attitude to teaching English in the classroom in the future.